Initial growth of bauhinia variegata trees under different colored shade nets and light conditions - Mazzini-Guedes, Renata Bachin [UNESP]; Lopes Pivetta, Kathia Fernandes [UNESP] (Univ Federal Vicosa, 2014)
Bauhinia variegata and B. variegata var. candida, commonly known as orchid trees, are small sized trees widely used for urban forestry and landscaping. Adult plants grow under full sun; in Brazil, however, seedlings are generally cultivated in commercial nurseries under natural half-shading. The objective of this study was to evaluate the influence of different colored shade nets and light conditions on the initial growth of B. variegata and B. variegata var. candida. The influence of six light conditions (red net with 50% shading; blue net with 50% shading; black net with 70% shading; black net with 50% shading; black net with 30% shading; and full sun) on the initial growth of B. variegata and B. variegata var. candida were evaluated along 160 days, and growth relationships were calculated. Seedlings showed more efficiency on the use of photoassimilated compounds when grown under full sun. Such condition is the most appropriate for seedling production of B. variegata and B. variegata var. candida, contradicting what has been performed in practice.

Bauhinia variegata e B. variegata var. candida, popularmente conhecidas como pata-de-vaca, são árvores de porte baixo muito usadas na arborização urbana e no paisagismo. Plantas adultas crescem sob sol pleno; no Brasil, no entanto, mudas são geralmente cultivadas em viveiros comerciais sob meia-sombra. O objetivo deste trabalho foi avaliar a influência de diferentes telas coloridas e condições de luminosidade no crescimento inicial de mudas de B. variegata e B. variegata var. candida. A influência de seis condições de luminosidade (tela vermelha com 50% de sombreamento, tela azul com 50% de sombreamento, tela preta com 70% de sombreamento, tela preta com 50% de sombreamento, tela preta com 30% de sombreamento e a sol pleno) no crescimento inicial das mudas foi avaliada ao longo de 160 dias, e relações de crescimento foram calculadas. As mudas foram mais eficientes no uso dos fotoassimilados quando cultivadas a sol pleno. Essa condição é a mais apropriada para a produção de mudas de B. variegata e B. variegata var. candida, contrariando o que vem sendo feito na prática.
Crescimento inicial de mudas de Bauhinia variegata sob diferentes telas coloridas e condições de luminosidade
Keywords: Orchid tree; Shading; Ornamental tree; Pata-de-vaca; Sombreamento; Árvore ornamental